Bayesian Estimation for Two Parameters of Gamma Distribution Under Precautionary Loss Function - Naji, Loaiy F.; Rasheed, Huda Abdullah (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In the current study, the researchers have been obtained Bayes estimators for the shape and scale parameters of Gamma distribution under the precautionary loss function, assuming the priors, represented by Gamma and Exponential priors for the shape and scale parameters respectively. Moment, Maximum likelihood estimators and Lindley’s approximation have been used effectively in Bayesian estimation.Based on Monte Carlo simulation method, those estimators are compared depending on the mean squared errors (MSE’s). The results show that, the performance of Bayes estimator under precautionary loss function with Gamma and Exponential priors is better than other estimates in all cases.